Republic of Uzbekistan - Joint World Bank-IMF Debt Sustainability Analysis - World Bank; International Monetary Fund (World Bank, Washington, DC, 2019)
Based on the Joint Bank-Fund Low-Income Country Debt Sustainability Analysis (LIC-DSA), Uzbekistan has a low risk of debt distress, with debt burden indicators below relevant thresholds in the baseline and all stress scenarios. Over the medium term, the public debt-to-GDP ratio is expected to increase moderately, while the total external debt-to-GDP ratio is expected to decline somewhat. In addition, large foreign exchange reserve buffers mitigate potential distress concerns. The debt sustainability analysis suggests that the most significant risks could result from worse-than-expected external flows (mostly lower remittances) and significantly lower exports. The government should carefully manage external borrowing to maintain Uzbekistan’s strong external position.